Language Policy Implementation and Academic Achievement of Pupils in Selected Primary Schools of Kaharo Sub-County Kabale District. - Koburonde, Stella (Kabale University, 2024)
This study explored the implementation of language policy and its impact on academic performance in selected primary schools in Kaharo Sub-county, Kabale District. The study aimed to assess the current level of learner performance, analyze key indicators of language policy implementation, and examine the relationship between language policy and academic achievement. A qualitative research approach was employed, gathering data through interviews with headteachers, teachers, and students, as well as document analysis and classroom observations. Basing objective one of this study, the findings reveal that the majority of students perform at an average level, and subjects like Mathematics and English are particularly challenging due to language barriers. This directly relates to assessing the current level of learner performance. Based on objective two, the findings emphasize key indicators such as teacher training, curriculum adaptation, and provision of learning materials. The emphasis on teacher training as the most important factor aligns with the objective of analyzing indicators of language policy implementation. Lastly, the findings show that language of instruction significantly affects student performance, particularly in English, and limited parental involvement due to language barriers further impacts learning. This directly ties to examining how language policy implementation influences academic achievement From the findings, the study recommended that; Improving learner performance in Kaharo Sub-county's primary schools requires continuous teacher development, increased parental involvement, and targeted academic support for struggling students. Ensuring effective language policy implementation involves regular monitoring, teacher training, and the provision of necessary instructional materials. Strengthening the relationship between language policy and learner achievement calls for data-driven strategies, community engagement, and the adoption of research-based teaching methods. Schools should implement additional academic support systems for learners lacking confidence in their ability to complete assignments and understand classroom content.